2018
DOI: 10.1002/bjs.10787
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in resected pancreatic mucinous cystic neoplasms

Abstract: Small indeterminate MCNs with no symptoms or features of concern may safely be observed as they have a low risk of malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 27 publications
4
16
1
1
Order By: Relevance
“…However, difference did not reach statistical significance (P=0.085). Association of weight loss and invasive carcinoma has been shown in multiple studies before (11,17,24). Correlation with malignancy was also present in our study (P=0.01).…”
Section: Etiological and Clinical Findings Associated With Malignancysupporting
confidence: 86%
See 1 more Smart Citation
“…However, difference did not reach statistical significance (P=0.085). Association of weight loss and invasive carcinoma has been shown in multiple studies before (11,17,24). Correlation with malignancy was also present in our study (P=0.01).…”
Section: Etiological and Clinical Findings Associated With Malignancysupporting
confidence: 86%
“…Unfortunately, we cannot provide a definitive explanation for the high overall proportion of men in our study. Multiple studies found that symptoms like weight loss, back pain and jaundice in patients undergoing surgery for MCN were associated with malignancy (23,24). In our study pain was more frequent in patients with invasive disease.…”
Section: Etiological and Clinical Findings Associated With Malignancysupporting
confidence: 57%
“…Recent studies on MCNs have shown that the risk of cancer in cysts less than 40 mm in size and without worrisome features is exceedingly rare [84,118]; therefore, in contrast to other guidelines, the revised European guidelines recommends surveillance of all MCNs <40 mm, following the same surveillance intervals as for a BD IPMN [57].…”
Section: Surveillancementioning
confidence: 99%
“…Of these cystic lesions, pancreatic cystic neoplasm (PCN) management is challenging and important in modern pancreatology. The challenge lies in the difficulty in accurately discerning completely benign PCNs from ones with potential for malignancy progression [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%